Analysis of Musical Meaning in Lyrics "Limpung Van Java” by Migsel Limpung in Batang Regency - Aji Setiawan; Irfanda Rizki Harmono Sejati (Jurnal Seni Musik, 2024)
This study analyzes the musical meaning in the lyrics of the song "Limpung van Java" by Migsel Limpung, which highlights the beauty and identity of Limpung City in Batang Regency. The primary goal of this research is to understand the message conveyed through the song's lyrics. Qualitative method with text analysis approach was used to explore the elements and connotations within the lyrics. The findings show that the use of repetition and a structured lyrical format creates a memorable and profound effect for listeners. The lyrics of "Limpung van Java" express pride in the city through phrases like "Kota Emping adalah julukannya" (Emping City is its nickname), which depict Limpung's distinctive products and cultural identity. In addition, the lyrics reflect strong values of brotherhood and community spirit in the city. The influence of the rocksteady genre in the music adds emotional depth and reinforces the message about the city’s beauty and friendliness. This research highlights the importance of understanding lyrical meaning and the impact of musical elements in appreciating the complexity and richness of local cultural expressions.